A panicked premonition - Laurie, Victoria (Laurie, Victoria. Psychic eye mystery series., 2017)
"The New York Times bestselling Psychic Eye Mystery series continues with P.I. Abby Cooper facing the ultimate locked room murder... Professional psychic and FBI consultant Abby Cooper has used her inner visions to get her out of many a scrape--and solvemany a crime--but she's about to face a murder scene that will put all her powers to the test. Abby's husband Dutch has a side business providing security and building panic rooms for wealthy clients. One morning, one of Dutch's partners, Dave, goes missing on his way to meet a client. Abby's intuition tells her something terrible has happened to him. Then two of Dutch's clients are found brutally murdered...inside their brand new panic room, and most of the evidence points to Dave as the killer. With the authorities racing to find and arrest him, Abby's got to use all her intuitive prowess to get to Dave first, discover the real killer, and save her husband's business. This is one case where Abby is positive there's far more to this mystery than meetsher inner eye